AKTIVITAS DAKWAH MELALUI PROGRAM SHALAT DHUHA PADA SISWA JURUSAN MULTIMEDIA SEKOLAH MENENGAH KEJURUAN (SMK) AL-HUDA KEDUNGWUNGU ANJATAN INDRAMAYU - Taufikin, Taufikin (Journal of Islamic Studies, 2023)
The school environment is a very good place for da'wah activities. School is a place to instill values of character, religion and humanity. Da'wah activities in schools are interesting to study. This study discusses the process and effects of the Dhuha prayer for students majoring in Vocational High School multimedia at Al-Huda Kedungwungu Anjatan Indramayu Vocational High School. The qualitative approach is the research approach used by the author in this study. Based on the type of research, this research is included in field research. As for the technique of collecting data through the process of observation, interviews and documentation that comes from both sources and from related documents which are then analyzed and interpreted in a qualitative descriptive form. The results of the research show that there is a process of da'wah activities for Al-Huda Kedungwungu Anjatan Indramayu Vocational High School (SMK) Students. In addition to the teaching and learning process at Al-Huda Kedungwungu Anjatan Vocational High School, Indramayu also includes da'wah activities in it. Based on the field, the Al-Huda Vocational School programmed Dhuha prayers to be held at schools which were then revived with da'wah activities including Al-Qur'an study and lectures.